Effect Of Chlorine Application In Simple Water Filtration Process On Iron Content Reduction In Groundwater - Tati Baina Gultom; Wibowo Ady Sapta (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Chlorine Ca(OCl)2 is another compound of chlor that can also remove various kinds of organic and inorganic substances, where these substances have oxidizing and reducing abilities. Two-valence iron (Fe2+) contained in groundwater is caused by the dissolution of water that seeps into the soil, so that the groundwater contains ferrous bicarbonate [Fe(HC03)2], where the water when used will harm the user. This experimental study aims to determine the effect of the dose of chlorine as an oxide in a simple water filtration process on reducing iron (Fe) levels in groundwater using water samples from the borehole complex of the Tanjungkarang Health Polytechnic, Department of Environmental Health. The research was conducted in the laboratory of the Environmental Health Department of Tanjungkarang Health Polytechnic, by making several doses of chlorine treatment in 1,000 ml of raw water, namely P1 = 0.5 gr, P2 = 1.0 gr, P3 = 1.5 gr, P4 = 2.0 gr and P0 without chlorine as a control. The treatment process is carried out by dosing chlorine, stirring (V = 70 rpm, t = 5 minutes), settling (t = 5 minutes) and filtering with a sand filter (0 = 0.1 - 1.5 mm, h = 20 cm) at a discharge of 100 ml / minute. The research results from 5 experiments showed the following experimental results of chlorine 0.0 gr (70.00%); 0.5 gr (84%); 1.0 gr (90%); 1.5 gr (97%) and 2.0 gr (98%). The statistical test used is the analysis of variance, where the hypothesis of the experimental results is rejected, which means that there is a significant difference in the effect of dosage as an oxidizer in a simple water filtration process on reducing iron (Fe) content in groundwater. Further research is needed for maximum results